A practical approach to English grammar and composition for high schools - Roberts, E. W. (Golden Books Centre, 2000)
This book embodies all the rules of grammar that a student should know. The grammatical problems that generally cause our students a lot of trouble have been thoroughly dealt with in this book. An ample number of exercises have been set on each chapter giving the student a lot of practice.